STRATEGI PENGEMBANGAN OBJEK WISATA SUMARU ENDO DI KABUPATEN MINAHASA (Development Strategy of Sumaru Endo Tourism Object in Minahasa District) - Yolanda E. Mukuan; J. V. Bobby Polii; Caroline B. D. Pakasi (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to determine priority and supporting strategies for the development of the Sumaru Endo Tourism Object, Minahasa Regency. This research was conducted from November to December 2021. The data used in this study were primaryÂ and secondary data. Primary data were obtained from FGDs and direct interviews with respondents. Secondary data wereÂ obtained from the North Sulawesi Provincial Tourism Office. The variables used in this study were indicators described through 4 important components in Tourism, namely: Attractions, Amenities, Accessibility and Accommodation which are further grouped into Internal Factors (Strengths and Weaknesses) and External Factors (Opportunities and Threats). The data analysis method used was SWOT analysis. The results showed that the Sumaru Endo Tourism Object Development Strategy had a high priority that could lead to rapid growth, which was the SO (Strengths Opportunities) strategy, especially